Innovating Content and Methods of Ideological and Political Education in the Context of the New Era - Zhang Qing (Ilmu Inovasi Nusantara, 2024)
This study identifies four significant challenges in China's current ideological and political education: outdated educational content that lacks relevance to modern developments, limited teaching methods that offer insufficient interactivity, a flawed evaluation system, and an unequal distribution of educational resources. These challenges have reduced the effectiveness of ideological education in shaping students' values and overall growth. This study aims to propose strategies that optimize and address these issues. It advocates for updating educational content to reflect contemporary trends, innovating teaching methods to foster greater engagement and interaction, improving the evaluation system with a stronger emphasis on skill development, and optimizing the allocation of educational resources to ensure a more balanced distribution. Analytically, the study reviews relevant literature and examines current educational practices across different institutions. The findings demonstrate that implementing these strategies can significantly enhance the quality and effectiveness of ideological and political education. Additionally, the study recommends that stakeholders in this field take immediate steps to adopt these changes while continually assessing the impact of these reforms. By doing so, the overall quality of education can be improved, supporting students' comprehensive development and growth. In the long term, these efforts are expected to create a more inclusive and effective educational system that aligns better with the needs of today's society